A clinical, microbiological, and pathological study of intestinal perforation associated with typhoid fever. - Nguyen, Q; Everest, P; Tran, T; House, D; Murch, S; Parry, C; Connerton, P; Phan, V; To, S; Mastroeni, P; White, N; Tran, T; et al. (2004)
One of the most serious complications of typhoid fever is intestinal perforation. Of 27 patients admitted to a provincial hospital in the Mekong Delta region of Vietnam who had gastrointestinal perforation secondary to suspected typhoid fever, 67% were male, with a median age of 23 years and a median duration of illness of 10 days. Salmonella enterica subspecies enterica serotype Typhi (S. Typhi) was isolated from 11 (41%) of 27 patients; of 27 patients, only 4 (15%) had positive cultures from gut biopsies. S. Typhi DNA was detected by polymerase chain reaction for all perforation biopsy samples. Detailed histological examination of the gastrointestinal mucosa at the site of perforation in all cases showed a combination of discrete acute and chronic inflammation. Acute inflammation at the serosal surface indicated additional tissue damage after perforation. Immunohistochemical results showed that the predominant infiltrating cell types at the site of perforation were CD68+ leukocytes (macrophages) or CD3+ leukocytes (T lymphocytes).